Genotoxic and hematological effects of chlorpyrifos exposure on freshwater fish Labeo rohita. (2nd January 2018) - Ismail, Muhammad; Ali, Rahat; Shahid, Muhammad; Khan, Muhammad Asaf; Zubair, Muhammad; Ali, Tayyaba; Mahmood Khan, Qaiser
Abstract: Chlorpyrifos is a commonly used organophosphate insecticide that causes toxicological effects in aquatic organisms especially in fish. This study determined the effects of chlorpyrifos on the genotoxic and hematological parameters of freshwater fish, Labeo rohita . The genotoxic effects of different sublethal concentrations of chlorpyrifos were investigated in the erythrocytes of Labeo rohita (commonly known as Rohu) using the Micronucleus test. Effects of chlorpyrifos on the hematological parameters of the fish were also observed. Fish specimens were exposed to three sublethal concentrations of chlorpyrifos viz., sublethal I (SL-I, 1/6th of LC50  = ∼73.8 μg/L), sublethal II (SL-II, 1/4th of LC50  = ∼110.7 μg/L) and sublethal III (SL-III, 1/2nd of LC50  = ∼221.4 μg/L) for 96 h. Blood samples were collected at every 24 h and were subjected to the Micronucleus assay. The observed micronucleus frequencies were concentration and time-dependent. The MN induction was significantly highest ( p  < 0.01) at all the concentrations on 96-h exposure. During the experimental period, hematological parameters like total erythrocytes count (TEC), hemoglobin (Hb) and packed cell volume (PCV) decreased, whereas total leukocytes count (TLC) increased. This study indicated that the Micronucleus assay is a useful tool to detect genotoxic potential of chlorpyrifos in fish.